Study of the Potential Use of Clay from Muratara Regency as Subtituent Materials for API Bentonite for Drilling Mud based on API RP 13B Mud Slurry Properties Tests - Azka R Antari; Machmud Hasjim; David Bahrin (Indonesian Journal of Environmental Management and Sustainability, 2020)
Bentonite, especially Sodium (Na) Bentonite is a type of clay that is used as a basis for water-based drilling mud in the of oil and gas wells drilling throughout the world including Indonesia, bentonite used in Indonesia is still partially imported from abroad. Sodium Bentonite can be substituted with ordinary clay which is treated by beneficiation throught addition of Na2CO3. The area of Musi Rawas Utara (Muratara) Regency of South Sumatra Province contains clay reserves resulting from pyroclastic deposit which will be investigated as potential subtitutional materials of imported API Bentonite. Clay samples from 6 different locations were prepared by first looking for the best % swell of sample beneficiation combination from all over the 36 combinations through the free swell test, the results obtained that the 4% BWOC Na2CO3 combination gave the best % swell. From this, 24 samples were prepared for various measurements of mud properties using standard equipment and procedures following the API RP 13 B for water-based mud with drilling grade Na-bentonite (API Bentonite) as standard material. The test includes 7 properties which are divided into 16 measurement units namely density, rheology, filtration, solid and liquid content, sand content, pH and methylene blue capacity etc. The test results show that the Na2CO3 beneficiation is able to change ionically the characteristics of the clay, but from the aspect of the suitability of the value of each test parameter to the standard value shows that none of the samples has full compatibility, which is mean that Muratara clay technically cannot be used as a substituent material of API Bentonite.